Adapting of Economic Development to Climate Change - Zajmi, Sandra (Journal of Economic Development, Environment and People, 2012)
Climate change is the most complex challenge that humankind has had to face in recent times. With each successive generation, redressing the imbalance will be more difficult. Diverse and complex requirements of maintaining life on Earth, collectively called the environment, can be caused both by natural, geophysical factors, and anthropogenic or social factors. There is a lot of evidence that the economic activity of mankind is a major anthropogenic factor in current turmoil of the environment on Earth. Since the middle of the nineteenth century, the anthropogenic impacts on the environment are becoming increasingly important, and undoubtedly dominate. Of all forms of economic activity the greatest impact have the activities related to energy production and use in various sectors. The link between environmental conditions and economic activities has become the subject of separate scientific disciplines that are dynamically developing in the second half of the twentieth century. Economic growth of the economies, especially of developed countries, in seventies and eighties of the twentieth century, drew attention to the growing international economic, political and ecological interdependence, particulary in terms of its ecological outcome. The future economic growth of all countries on the planet thus becoming a global problem. In this context, more attention must be paid to the relationship between population, resources, and environmental outcomes on one side, and long-term sustainable economic development on the other side. In the recent time there have been noticeable the increasing number of problems that are becoming global: economic, social and energy problems, and contain ecological basis. Human decisions and acivities are dependent on ethics and view of the world, and this view depends on the culture, tradition, achieved level of development and so on. Therefore, it is necessary to adjust economic development to climate change, where a great importance plays a cooperation between the public and private sector.